FILSAFAT ISLAM NUSANTARA DAN MANIFESTASI KEARIFAN LOKAL - Andre Saputra; Surajiman Perkasa (INTELIGENSIA MEDIA, 2023)
Islam Nusantara is a model of thinking, understanding and practicing Islamic teachings packaged through considerations of culture or traditions that developed in the Southeast Asian region (but this study is limited to Indonesia). Thus reflecting a methodological nuanced Islamic identity. When this identity was socialized among Muslims, especially its thoughts, it was responded with controversial responses: there were those who rejected the Nusantara Islamic identity because there was only one Islam, namely Islam taught by the Prophet. On the other hand, many Islamic thinkers accept the archipelago's Islamic identity. For them, there is only one Islam that is substantively correct, but its expressions are very diverse, including Islam Nusantara. This Islam is displayed (thought, understood and practiced) through a cultural approach. The result gave birth to models of thought, understanding and practice of Islamic teachings that are friendly, moderate, inclusive, tolerant, peace-loving, harmonious and respect diversity. This kind of Islamic diversity occurs because of the encounter of Islam with local culture, especially Java, which is commonly called cultural acculturation. Indonesian Islam should be an example of such a way of Islam. This soothing Islamic model needs to be published internationally and is expected to be able to abort the world's perception that Islam is full of violence.